How Do Regulated Nurse Professionals in Alberta Assess Geriatric Depression in Residential Care Facilities?. Issue 3 (22nd September 2020) - Azulai, Anna; Walsh, Christine A.
ABSTRACT: Although geriatric depression is a prevalent, serious, and under-recognized mental health condition in residential care facilities, there is a dearth of related research in Canada. This exploratory mixed methods study examines the perspectives and practices of regulated nurse professionals on assessment of geriatric depression in residential care facilities in Alberta. Findings from the quantitative surveys ( n = 635) and qualitative interviews ( n = 14) suggest that geriatric depression is not systematically assessed in these care settings due to multiple challenges, including confusing assessment protocol, inconsistent use and contested clinical utility of current assessment methods in facilities, limited availability of mental health professionals in facilities, and the varied views of regulated nurse professionals on who is responsible for depression assessment in facilities. Implications and future research directions are discussed.